Perceptions from scholars in education on Sino-Malaysian higher education cooperation under the background of one belt and one road initiative: a case study - Zhai, Xiuwen; Razali, Abu Bakar; Luo, Shengyao; Zhang, Songcun; Mai, Hongyu (Human Resource Management Academic Research Society, 2023)
The Sino-Malaysian higher education cooperation within the One Belt and One Road Initiative framework has gained momentum in recent years, fostering academic exchange, cultural understanding, and economic growth between China and Malaysia. However, there is a need to understand the perceptions of education scholars involved in these collaborations to identify challenges, opportunities, and areas for improvement. This research aims to bridge the gap by examining their perspectives and ultimately enhancing the effectiveness and sustainability of this cooperative venture. This research aims to provide valuable insights and recommendations that can contribute to the enhancement and sustainable development of Sino-Malaysian higher education cooperation. By understanding education scholars' perceptions, policymakers and educators can design more effective strategies. The study seeks to share insights for a vibrant educational ecosystem that nurtures cross-cultural understanding, knowledge exchange, and sustainable development between China and Malaysia.